Edukasi Stunting Melalui Sosialisasi Pola Asuh Terhadap Perkembangan Emosi Anak - Sholihah, Mar'atus; Mutmainah, Siti; Jayanti, Siti Nur; Masruri, M. Yazid; Mansur, Ulil; Ghozali, Muhtar (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2023)
Currently, in Indonesia and even in the world, some children are affected by stunting. This is due to poor nutrition and parenting patterns affecting children’s emotional development. Poor parenting is one of the factors that cause stunting in children. Child care can be implemented by providing nutritious food, health care, and good parenting habits. It is expected that the existence of stunting education through the socialization of parenting patterns on children's emotional development can become an alternative program that educates parents to take care of the children so that it can reduce the number of stunting children in Munder Village, Yosowilangun District, Lumajang Regency. This community development research was developed due to there are many children who experience stunting, one of the causes is poor parenting patterns so that children have unstable and uncontrolled emotional development. This parenting socialization applied lecturing and question-answer method. The socialization ran smoothly, parents responded well and listened to the speakers enthusiastically. Parents need to understand stunting because, through this socialization activity, they can practice the parenting pattern method and can spread the knowledge to their peers to provide a good and proper upbringing for their children.